1980
DOI: 10.3382/ps.0592111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drug Additives and Type of Diet on Methionine Requirement for Growth, Feed Efficiency, and Feathering of Broilers Reared in Floor Pens

Abstract: Two experiments were conducted in litter floor pens with broiler-type chicks to determine the effect of amprolium-ethopabate, lasalocid, monensin, and lincomycin on growth, feed efficiency, and feathering responses to graded levels of methionine. In Experiment 1, a pea-corn diet was supplemented with 5 levels of methionine (0 to .3%) in combination with amprolium-ethopabate (125 to 140 ppm), lasalocid (125 ppm), or monensin (121 ppm). In the second experiment, two different types of diets (corn-soy and pea-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…Because females exhibit a higher feed intake per body weight gain, this would result in a higher milligram dose rate per body weight gain of anticoccidial and thus possibly exacerbate weight depression in the females. Several reports have concluded that ionophore medications can depress body weights through reduced feed intake (Morrison et al, 1979;Patel et al, 1980;Willis and Baker, 1981), but other studies have found no effect (Frigg and Broz, 1983;Gard et al, 1975). These contradictory findings may be partially atrributable to differing levels of medication.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because females exhibit a higher feed intake per body weight gain, this would result in a higher milligram dose rate per body weight gain of anticoccidial and thus possibly exacerbate weight depression in the females. Several reports have concluded that ionophore medications can depress body weights through reduced feed intake (Morrison et al, 1979;Patel et al, 1980;Willis and Baker, 1981), but other studies have found no effect (Frigg and Broz, 1983;Gard et al, 1975). These contradictory findings may be partially atrributable to differing levels of medication.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has been reported that these drugs may depress growth performance of broiler chickens not challenged with coccidia (Morrison et al, 1979;Damron et al, 1977;Patel et al, 1980). This growth depression is attributable to reduced feed intake; thus, compensatory growth is often noted when these anticoccidials are withheld from finisher diets (McDougald and McQuiston, 1980).…”
Section: Introductionmentioning
confidence: 95%
“…Open Journal of Animal Sciences As reviewed by Leeson and Walsh [9], the nutrient supply impacts on feather growth and development. Stimulated feather growth was observed with increasing dietary CP and SAA supply [18] [20] [22], mainly due to varying body proportion of feathers, connective tissue and muscle tissue [59]. Additionally, more feathers were found on the litter following a high protein diet [58] indicating faster feather development with subsequent moult.…”
Section: Discussionmentioning
confidence: 99%
“…However, this coccidiostat often depresses growth performance when included in the diet of healthy chicks (Gard et al, 1975;Damron et al, 1977). Patel et al (1979) concluded that the methionine requirement of chicks was reduced in the presence of monensin due to the growth depressing effect of the drug. In contrast, research from our laboratory has indicated that monensin has no effect on the chick's sulfur amino acid (SAA) requirement (Baker and Robbins, 1979;Willis and Baker, 1980).…”
Section: Introductionmentioning
confidence: 96%